Comparison of curved prestressed concrete bridge population response between area and spine modeling approaches toward efficient seismic vulnerability analysis. (1st November 2017) - Seo, Junwon; Rogers, Luke P.
Highlights: Two finite element modeling approaches were proposed. The two approaches were applied to curved PSC bridges. Seismic response for the bridges was examined. Seismic vulnerability for the bridges was assessed. Abstract: This paper presents two finite element modeling approaches for seismic evaluation of curved precast-prestressed concrete (PSC) I-girder bridges and compares the results in a statistical and graphical manner. These approaches, including area and spine models, were applied to a simply-supported, curved PSC I-girder bridge under an ensemble of 3D synthetic ground motions. Along with performing non-linear time history (NLTH) analyses of the bridge to capture its separate seismic response, the efficiency of each approach was evaluated with respect to execution time and each was compared. This comparison reveals that the seismic responses that were computed at low computational cost from the spine approach are reasonably analogous to those from the area model. Seismic fragility curves of a portfolio of curved PSC bridges using the spine approach are also created to assess their vulnerability and then compared to those gained from past studies. This comparison shows a reasonable agreement for the PSC portfolio.